2018
DOI: 10.1007/s00417-018-3906-z
|View full text |Cite
|
Sign up to set email alerts
|

MiSight Assessment Study Spain (MASS). A 2-year randomized clinical trial

Abstract: MiSight contact lens wear reduces axial elongation and myopia progression in comparison to distance single-vision spectacles in children. ClinicalTrials.gov Identifier: NCT01917110.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
190
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(203 citation statements)
references
References 44 publications
8
190
3
2
Order By: Relevance
“…A significant slowing of myopia was observed with test contact lenses and results from this trial adds to the growing evidence that demonstrates that it is feasible to slow the progression of myopia …”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…A significant slowing of myopia was observed with test contact lenses and results from this trial adds to the growing evidence that demonstrates that it is feasible to slow the progression of myopia …”
Section: Discussionmentioning
confidence: 56%
“…More recent studies in animal models found the peripheral retina to play an active role in emmetropization and refractive error development, and peripheral or off‐axis hyperopic defocus was considered to be instrumental in axial elongation . A number of innovative lens designs aimed at reducing off‐axis defocus and inducing myopic defocus were assessed in animal and human clinical trials and shown to reduce the axial elongation of the eye …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, myopia control has been attempted with commercially available simultaneous‐vision bifocal/multifocal soft contact lenses, as well as lenses with novel dedicated myopia control designs. Almost all of these soft contact lenses extend the depth of focus of the eye . If children under‐accommodate by utilising the more proximal retinal conjugate plane created by the “add” power of the lens, the “distance” optics will create significant hyperopic defocus, which may diminish or eliminate the myopia control effect of the lens.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2011 and 2019, 9 randomised trials with soft dual focus contact lenses were published . Four studies used lenses with a concentric design; the other studies used lenses with a progressive design.…”
Section: Myopia Managementmentioning
confidence: 99%